Association of Psychosocial Work Hazards With Depression and Suboptimal Health in Executive Employees. Issue 7 (July 2016) - Hsu, Sandy Huey-Jen; Chen, Duan-Rung; Cheng, Yawen; Su, Ta-Chen
Abstract : Objectives: This study aims to investigate whether psychosocial work-related hazards, measured by workplace justice and employment insecurity, are associated with depression and suboptimal health status in Taiwan's executive-level employees. Methods: There were 365 executives who have received a series of cardiovascular health examinations, blood sampling, and self-reported questionnaires, which included the psychosocial work-related hazards and the CES-D scale. Suboptimal health status was defined as the presence of dyslipidemia or prediabetes. Results: Executive-level employees perceived lower workplace justice and higher employment insecurity and had a significantly higher risk of depression (CES-D scores ≥16 or ≥23). However, workplace justice was identified as a significant determinant factor that was negative for dyslipidemia but protective for prediabetes. Conclusion: This study supports the fact that psychosocial work-related hazards can independently contribute to the risk of developing depression, prediabetes, and dyslipemia in executives.